Joint Associations of Diet, Lifestyle, and Genes with Age-Related Macular Degeneration - Meyers, Kristin J; Liu, Zhe; Millen, Amy E; Iyengar, Sudha K; Blodi, Barbara A; Johnson, Elizabeth; Snodderly, D Max; Klein, Michael L; Gehrs, Karen M; Tinker, Lesley; Sarto, Gloria E; Robinson, Jennifer; et al. (Ophthalmology (Rochester, Minn.), 2015)
Unhealthy lifestyles have been associated with increased odds for age-related macular degeneration (AMD). Whether this association is modified by genetic risk for AMD is unknown and was investigated. Interactions between healthy lifestyles AMD risk genotypes were studied in relation to the prevalence of AMD, assessed 6 years later. Women 50 to 79 years of age in the Carotenoids in Age-Related Eye Disease Study with exposure and AMD data (n=1663). Healthy lifestyle scores (0-6 points) were assigned based on Healthy Eating Index scores, physical activity (metabolic equivalent of task hours/week), and smoking pack years assessed in 1994 and 1998. Genetic risk was based on Y402H in complement factor H (CFH) and A69S in age-related maculopathy susceptibility locus 2 (ARMS2). Additive and multiplicative interactions in odds ratios were assessed using the synergy index and a multiplicative interaction term, respectively. AMD presence and severity were assessed from grading of stereoscopic fundus photographs taken in 2001-2004. AMD was present in 337 women, 91% of whom had early AMD. The odds of AMD were 3.3 times greater (95% confidence interval [CI], 1.8-6.1) in women with both low healthy lifestyle score (0-2) and high-risk CFH genotype (CC), relative to those who had low genetic risk (TT) and high healthy lifestyle scores (4-6). There were no significant additive (synergy index [SI], 1.08; 95% CI, 0.70-1.67) or multiplicative (Pinteraction=0.94) interactions in the full sample. However, when limiting the sample to women with stable diets before AMD assessment (n=728) the odds for AMD associated with low healthy lifestyle scores and high-risk CFH genotype were strengthened (odds ratio, 4.6; 95% CI, 1.8-11.6) and the synergy index was significant (SI, 1.34; 95% CI, 1.05-1.70). Adjusting for dietary lutein and zeaxanthin attenuated, and therefore partially explained, the joint association. There were no significant additive or multiplicative interactions for ARMS2 and lifestyle score. Having unhealthy lifestyles and 2 CFH risk alleles increased AMD risk (primarily in the early stages), in an or additive or greater (synergistic) manner. However, unhealthy lifestyles increased AMD risk regardless of AMD risk genotype.